The Urgency of Regulations Concerning the Bankruptcy of State-Owned Enterprises - Baitiya Muharrami Ardinuri; Natasya Augustine Rixstriwati; Akmal Fata Mursidin; Radyananda Argo Herlambang; M. Ade Dharma Praja (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Bankruptcy of State-Owned Enterprises (BUMN Persero) The chosen theme is motivated by the absence of regulations regarding limitations on bankruptcy petitions for BUMN Persero, which has caused differences in opinion leading to legal deviations in practice. Regulations on bankruptcy petitions for BUMN Persero can serve as a reference, but they must still be adjusted considering the fundamental special characteristics of BUMN. The legal materials obtained by the author will be analyzed using descriptive and evaluative analysis techniques. In this regard, the author collects legal materials such as legislation and also conducts source searches on the internet by accessing official sites like e-books, e-journals, or official articles published online. Based on the research using the above methods, the author finds that there are philosophical, juridical, and sociological urgencies that make regulations regarding bankruptcy petitions for BUMN Persero necessary. These regulations aim to prevent misinterpretations concerning the parameters of limitations on BUMN operating in the public interest sector, and banking regulations for BUMN Persero can prevent differences of opinion that result in legal deviations in practice. Law No. 37 of 2004 regulates bankruptcy of BUMN but does not clearly regulate bankruptcy petitions specifically for BUMN Persero, so it requires revision or additions. However, this law can be used as a reference in analyzing bankruptcy regulations for BUMN Persero. There are two models of bankruptcy petitions depending on the legal subject or the status of the company being petitioned for bankruptcy. It can be understood that bankruptcy petitions for BUMN Perum are filed by the Minister of Finance, whereas for BUMN Persero, if 100% or the entire share ownership is held by the State, the Minister of Finance can file the bankruptcy petition. However, if this is not applicable, the Bankruptcy Law does not apply because the Minister of Finance acts as the manager of State Assets.